2002
DOI: 10.1007/s00792-002-0276-5
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Dry Valley mineral soils contain unexpectedly high levels of microbial biomass

Abstract: We have applied bioluminescent ATP detection methods to microbial enumeration in Antarctic Dry Valley mineral soils, and validated our ATP data by two independent methods. We have demonstrated that ATP measurement is a valid means of determining microbial biomass in such sites, and that the desiccated surface mineral soils of the Antarctic Dry Valleys contain cell numbers over four orders of magnitude higher than previously suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 19 publications
4
63
2
Order By: Relevance
“…In the absence of vascular plants, the mineral soils of the Dry Valleys are dominated by microbial communities. Contrary to earlier assumptions, which predicted low community complexity and spatial heterogeneity, recent molecular-based research (for example, Cowan et al, 2002;Aislabie et al, 2006;Barrett et al, 2006b;Smith et al, 2006; TD Niederberger, IR McDonald, AL Hacker, RM Soo, JE Barrett, DH Wall, SC Cary unpublished) has shown that the Dry Valley soils contain a much more diverse community assemblage than would have been expected given the harsh environmental conditions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the absence of vascular plants, the mineral soils of the Dry Valleys are dominated by microbial communities. Contrary to earlier assumptions, which predicted low community complexity and spatial heterogeneity, recent molecular-based research (for example, Cowan et al, 2002;Aislabie et al, 2006;Barrett et al, 2006b;Smith et al, 2006; TD Niederberger, IR McDonald, AL Hacker, RM Soo, JE Barrett, DH Wall, SC Cary unpublished) has shown that the Dry Valley soils contain a much more diverse community assemblage than would have been expected given the harsh environmental conditions.…”
Section: Discussionmentioning
confidence: 73%
“…They are characterized by extremely low temperatures and precipitation, the latter occurring only as snow, which is largely lost by sublimation (Doran et al, 2002). These valleys are considered to be the coldest, most arid deserts on Earth (Cowan et al, 2002;Doran et al, 2002). In general, most of the mineral soils of the valley floors lack any visible cyanobacterial or algal growth, whereas biomass is more apparent in glacial streams and lake margins (Taton et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Antarctic soils were reported to be depauperate in terms of bacterial abundance and diversity (Flint and Stout 1960), with many soils reported to be sterile (Horowitz et al 1972). The recent application of molecular techniques has greatly improved the resolution of microbial analyses and revealed that bacterial communities are far more abundant (Cowan et al 2002) and diverse (Tindall 2004;Smith et al 2006;Barrett et al 2006b;Niederberger et al 2008;Cary et al 2010) than initially understood.…”
mentioning
confidence: 99%
“…First, Pointing et al rightly suggest that an upward revision of standing biomass (and by implication, productivity) in these Antarctic soils is probably warranted. This view is supported by an earlier study (11), albeit in the low-altitude, maritime-influenced Miers Valley, which demonstrated using ATP, lipid, and DNA quantification that standing biomass was in the range of 10 6 to 10 8 cells⅐g Ϫ1 soil, orders of magnitude higher than determined by microscopic and culture-dependent estimates (see, for example, ref. 12).…”
mentioning
confidence: 56%